Endovascular Therapy for Nonischemic vs Ischemic Complicated Acute Type B Aortic Dissection. (February 2020) - Eleshra, Ahmed; Kölbel, Tilo; Panuccio, Giuseppe; Rohlffs, Fiona; Debus, E. Sebastian; Tsilimparis, Nikolaos
Purpose: To report a single-center experience with thoracic endovascular aortic repair (TEVAR) for complicated acute type B aortic dissection (cATBAD) comparing patients with vs without end-organ ischemia.Materials and Methods: Between November 2010 and December 2017, 64 patients (mean age 64.8±12.5 years; 49 men) underwent TEVAR for cATBAD. Patients were grouped into 2 cohorts: nonischemic (39, 61%) patients with unrelenting pain, early progressive aortic dilatation, uncontrolled hypertension, or rupture, and ischemic (25, 39%) patients with visceral, renal, lower extremity, or spinal cord hypoperfusion.Results: Mean time from diagnosis to treatment was 7.5 days (range 1–32) in the nonischemic group vs 2.3 days (range 1–14) days in the ischemic group (p=0.007). Fourteen (56%) of 25 ischemic cATBAD patients had stents implanted in the renovascular branch vessels, while 4 (16%) patients had stents implanted in the iliac arteries. When branch vessel cannulation failed, fenestrations were made in the intimal flap to improve perfusion of the involved branch (n=5). In the nonischemic group, 3 arteries were stented owing to atherosclerotic stenosis. Technical success was achieved in 62 (97%) of 64 patients; despite stenting, 2 patients had low renal artery perfusion on final angiography. There were no statistically significant differences in early or late outcomes between the nonischemic vs ischemic cATBAD patients. Six (9%) patients died within 30 days: 2 (5%) in the nonischemic group vs 4 (16%) in the ischemic group. Major complications (1 stroke, 2 cases of paraplegia, 1 retrograde type A dissection, and 1 case of bowel ischemia) occurred only in the nonischemic group. The mean follow-up was 28 months. Late endoleaks were observed in 3 (8%) nonischemic patients and 1 (4%) ischemic patient. Reinterventions were required in 7 (18%) nonischemic patients and 4 (16%) ischemic patients.Conclusion: TEVAR is an effective and safe method of treating cATBAD. Early intervention in ischemic cATBAD may have played a significant role in the lack of significant difference between ischemic and nonischemic cATBAD outcomes. Direct visceral reperfusion through branch vessel stenting during TEVAR may be crucial in achieving good outcomes in ischemic cATBAD.